A Service of Love - McPartlan, Paul (Book collections on Project MUSE., 2013)
In this short study, the author - a member of the international Roman Catholic-Orthodox theological dialogue - presents a proposal, carefully argued both historically and theologically, for a primacy exercising a service of love in a reconciled church, West and East.